Chain of blame how Wall Street caused the mortgage and credit crisis - Muolo, Paul.; Padilla, Mathew (Hoboken, N.J. : John Wiley & Sons, 2008)
In the summer of 2007, the subprime empire that Wall Street had built all came crashing down. Banks like Countrywide and non-banks such as New Century Financial--all financed by Bear Stearns, Goldman Sachs, Merrill Lynch, Lehman Brothers and others--were in danger of closing, or actually failing. On average, 50 lenders a month were going bust. Chain of Blame will chronicle the disaster, focusing on the players - the executives on Wall Street but also the lenders and brokers. It's a national story of greed and avaraice, one that hasn't come down the pike since the S&L scandal.--From publisher description.
Includes bibliographical references (p. 309-317) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2021. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Mortgages -- United States; Mortgage loans -- United States; Financial crises -- United States; Stock exchanges -- United States; Electronic books